TARI-TARIAN LITURGI BULAN BUDAYA SEBAGAI TARIAN PENERIMAAN TERHADAP “YANG LAIN” DI GMIT - Hermanus, Rio Rocky (Melo: Jurnal Studi Agama-agama, 2025)
Abstract: The context of the Evangelical Christian Church in Timor which has a diversity of tribes and cultures is an opportunity for theological efforts that are appropriate to the context. On the other hand, the theological efforts in question are theologizing to accept "the others" in the diversity of local cultures. This writing uses a qualitative-descriptive method with an ethnographic approach for the way to - through, following (meta) and the path, way, direction (hodos) approaching a topic of study on the Liturgy of the Cultural Month (LBB). The results of this study are a form of acceptance of others for GMIT through dances in LBB. GMIT accepts others from the perspective of Christian faith to create a life of mutual acceptance in a diverse context in GMIT. Abstrak: Konteks Gereja Masehi Injili Di Timor yang memiliki keberagaman suku dan budaya adalah sebuah peluang bagi upaya berteologi yang sesuai dengan konteks. Di sisi lain, upaya berteologi yang dimaksud adalah berteologi untuk menerima “yang lain” dalam kepelbagaian budaya lokal. Penulisan ini menggunakan metode kualitatif-deskriptif dengan pendekatan etnografi untuk cara menuju–melalui, mengikuti (meta) dan jalan, cara, arah (hodos) mendekati sebuah pokok kajian tentang Liturgi Bulan Budaya (LBB). Hasil dari penelitian ini adalah bentuk dari penerimaan terhadap yang lain bagi GMIT melalui tari-tarian dalam LBB. GMIT menerima yang lain dari perspektif iman Kristen untuk menciptakan kehidupan yang saling menerima dalam konteks yang beragam di GMIT.